2005
DOI: 10.1093/jn/135.2.172
|View full text |Cite
|
Sign up to set email alerts
|

The Flavonoid Phloretin Suppresses Stimulated Expression of Endothelial Adhesion Molecules and Reduces Activation of Human Platelets

Abstract: Atherosclerosis is a chronic inflammatory disease accompanied by the expression of endothelial adhesion molecules. Phloretin is a plant-derived phytochemical that is mainly present in apples. Because phloretin is reported to promote antioxidative activities, we investigated the effects of phloretin on cytokine-induced expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and endothelial leukocyte adhesion molecule-1 (E-selectin) in human umbilical vein endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 41 publications
1
65
0
1
Order By: Relevance
“…17) Phloretin suppresses the stimulated expression of endothelial adhesion molecules. 18) All this regulatory activity of proinflammatory molecules including iNOS by certain chalcones may contribute to their anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…17) Phloretin suppresses the stimulated expression of endothelial adhesion molecules. 18) All this regulatory activity of proinflammatory molecules including iNOS by certain chalcones may contribute to their anti-inflammatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Phloretin accounts in part for the antioxidant capacity of apples, and phloretin has also been revealed to have anticarcinogenic activities (50) and in vitro anti-inflammatory activity on colon epithelial cells (17) and on vein endothelial cells (41). In a previous study, it was shown that phloretin downregulated the mRNA levels of most tested proinflammatory genes (NF-B, TNF-␣, interleukin-8, CXCL3, CXCL10, signal transducer and activator of transcription 1, and interferon gamma-induced protein 10) in human colon epithelial cells in vitro (17).…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous flavonoids, phloretin is a dihydrochalcone, a type of polyphenol mainly found in apples (about 5 mg/100 g of fresh apple) and strawberries. Phloretin has various biological functions, such as antioxidative (36), anticarcinogenic (50), and estrogenic (6) activities and inhibition of cardiovascular disease (10,41). Recently, several other flavonoids showed the ability to inhibit the biofilm formation of Streptococcus mutans (22), Aeromonas hydrophila (18), and Escherichia coli O157:H7 (48).…”
mentioning
confidence: 99%
“…Phloretin is mainly found in apples and strawberries [8][9][10]. It has numerous biological properties, including reduction of human platelets activity, competitive inhibition of sodium-glucose cotransporters (SGLTs), inhibition of cardiovascular disease and anticarcinogenic activity [11,12]. Compared with other flavonoids, however, few studies have investigated the anti-tumor potential of phloretin.…”
Section: Introductionmentioning
confidence: 99%